Integrated work-based learning (I-WBL) model development in light vehicle engineering competency of vocational high school - Suyitno Suyitno; Pardjono Pardjono (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This research is to (1) analyze the implementation of new field project; (2) develop conceptual model of WBL integrated to industry; (3) test the validity of WBL integrated; (4) test the effectiveness of integrated WBL. This is educational and development research using randomized pretest-posttest and controlled group design. The population was all vocational school students. The research was conducted from March to December 2016. Data were collected by listing, using observation sheet, interviewing guidline and documenting. Validating was done by some experts. The data were analyzed in descriptive and multivariate Analysis of Variance by SPSS.17. The result shows that (1) the implementation field project has some weaknesses; (a) the schools are less prepared to plan the program, place and MoU; (b) schools never formally invite outside; (c) not all schools have a guidance to do a field project and schools only measure student's skill aspect after doing field project; (2) developing model through philosophical level, theoritical level, methodological level, dan classroom practice; (3) after validation of the guidance book by 12 experts, it shows the average score up to 4; (4) The group using WBL is more effective than that using field project in increasing the student'.